Perubahan Pemanfaatan Ruang Di Kawasan Cagar Budaya Benteng Fort Rotterdam Kota Makassar - Pratiwi Juniar Achmad Gani, Muhammad Zaki (Celebes Engineering Journal, 2019)
Following the purpose of its construction, the fort has a function as a place of refuge for those who live in it. Nowadays there are more and more various activities in the Fort Rotterdam area, causing the dynamics of life to become increasingly diverse. This is marked by the emergence of other activities besides activities related to the fort which has been designated as a cultural heritage area of ​​Makassar City. This study aims to determine the changes in spatial use that occur and the direction of space used in the Fort Rotterdam cultural heritage area. The research to be carried out is non-experimental and qualitative descriptive which will examine the conceptual application model of the problems in the field spatially with spatial analysis techniques. The results of the study found that (1) changes in activity are the most influential factors for changes in space use, (2) increases in changes in space use at the macro scale occur in the use of green open spaces into office and service areas, and (3) changes in space utilization on a scale The largest micro-structure occurs by using buildings to become museums.